PSYCHOLOGICAL PROFILING OF SELF- ENTREPRENEURS IN THE MARRAKECH-SAFI REGION - CHERKAOUI , Roquia (Revue Internationale des Sciences de Gestion, 2024)
This research explores the psychological profile of self-entrepreneurs in the Marrakech Safi region, focusing on the personality traits, skills and behavioral tendencies that characterize these individuals. Drawing on psychological studies and academic research, the article offers an in-depth look at the psychological characteristics that distinguish emerging entrepreneurs. The aim of this study is to help people interested in entrepreneurship to better apprehend their own potential and strengthen their skills. It is crucial to underline the importance of a thorough psychological self-assessment, a step often neglected or even ignored by entrepreneurs who hasten to focus all their efforts on the economic, commercial and legal feasibility of their project. What's more, this research provides invaluable support to support structures, enabling them to adopt the best posture for each profile. Support during the early stages of an entrepreneurial project is of particular importance, as it can greatly contribute to the success of the creative act as well as to the development of the fledgling business. This analysis is based on a sample of 194 young Moroccans aged under 45, drawn from a source population enrolled in the self-employment support program in the Marrakech Safi region. A typological analysis of the "two-step" data revealed discriminating factors that contributed to the creation of specific profiles for the project managers interviewed.